Peningkatan Kemampuan Tata Kelola BUMDES Desa Sambirata Kecamatan Cilongok - Astika Nurul Hidayah; Selamat Widodo; Naelati Tubastuvi (Jurnal Pengabdian Kepada Masyarakat Kalam, 2022)
Sambirata Village, Cilongok District has natural wealth that has the potential to be developed for the progress of the village and the welfare of its people. This natural potential is in the form of a very beautiful natural environment that is still maintained, and allows it to be developed as a tourist destination. In addition, Sambirata has the advantage of producing cardamom which has been well managed by local farmer groups, although marketing is still limited. This potential can actually be further developed under the management of the Village-Owned Enterprises (BUMDES) Sambirata, Cilongok District. However, at this time, BUMDES Sambirata has not been able to play an optimal role in managing the potential of the village. Therefore, an effort is needed to build awareness of the importance of governance capabilities and legality management of institutions so that village institutions can carry out their roles and functions optimally in order to advance the village and improve community welfare in Sambirata Village, Cilongok District, Banyumas Regency.